Framing energy cultures : materiality and motivators of household energy transition in Nepal - Kok, Dianne; Brogaard, Sara; Islar, Mine ; 0000-0001-9479-4734; Sharma, Sudhindra; Thapa, Rabina (Sustainability Science, 2025)
Nepal has made major progress in expanding its national electricity grid, creating the potential for a double transition as increased access to electricity benefits the energy-poor while setting the infrastructural ground for a transition to renewable energy sources. However, despite increased access, many households in Nepalcontinue to rely on traditional and transition fuels such as firewood and gas. This can be problematic as without the actual adoption of modern energy sources, energy development may be limited in relation to socioeconomic progress and transition toward an environmentally sustainable energy system. Informed by qualitative semi-structured interviews, this article applies the Energy Cultures Framework to model the materiality, motivators, and activities of household energy consumption in Nepal. This method and framework allow for reflection on the drivers and barriers around energy transition as perceived by households themselves. We find that although many households are satisfied with the convenience of gas and electricity, major barriers to modern energy use, such as income, knowledge, habits, and unreliable supply, remain. Future change is mostly motivated by households’ desire to live a convenient and healthy life and relies on locally informed policy that is conscious of urban and rural energy wants and needs.
Publisher Copyright: © The Author(s) 2025.
Keywords: Energy justice; Materiality; Meaning; Practice; Sustainability cultures; Sustainable development